Theater - Loxton, Howard (Austin, Tex. Steck-Vaughn Library, 1990)
An overview of theater as an art form with emphasis on the English-speaking theater. Includes information on the history of the theater, acting methods, staging, putting on a play, and theater careers.
Bibliography: p. 44
Includes index.
Keywords: Theater -- Juvenile literature; Theater